2012
DOI: 10.1248/cpb.c12-00563
|View full text |Cite
|
Sign up to set email alerts
|

Improved Supersaturation and Oral Absorption of Dutasteride by Amorphous Solid Dispersions

Abstract: In this study, amorphous solid dispersions containing dutasteride and various excipients, manufactured by spray-drying processes, were characterized to determine the effects on their ability to form supersaturated solutions and to identify the effects of supersaturation on increasing the bioavailability of dutasteride. The excipients included Eudragit E, hydroxypropyl-β-cyclodextrin (HP-β-CD), hydroxypropyl cellulose (HPC), hydroxypropylmethyl cellulose (HPMC), and polyvinylpyrrolidone (PVP K30). A solid dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Dutasteride was extracted from the plasma matrix by protein precipitation, and drug concentrations in the plasma samples were analyzed using liquid chromatography with tandem mass spectrometry as previously reported. 6 The pharmacokinetic parameters, ie, AUC 0→24h (area under the concentration-time curve), C max (peak concentration), and T max (time to peak concentration), were calculated using noncompartmental analysis. Relative bioavailability was calculated using the following equation, with the commercial product used as a reference: relative bioavailability (%) = AUC test / AUC reference × 100.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Dutasteride was extracted from the plasma matrix by protein precipitation, and drug concentrations in the plasma samples were analyzed using liquid chromatography with tandem mass spectrometry as previously reported. 6 The pharmacokinetic parameters, ie, AUC 0→24h (area under the concentration-time curve), C max (peak concentration), and T max (time to peak concentration), were calculated using noncompartmental analysis. Relative bioavailability was calculated using the following equation, with the commercial product used as a reference: relative bioavailability (%) = AUC test / AUC reference × 100.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…[6][7][8][9] Among these formulations studied, the Eudragit E nanoparticle suspension afforded a dutasteride bioavailability 5.5-fold higher than that afforded by a 0.3% w/v Soluplus suspension (mean particle size 1.92 µm). However, use of the Eudragit E nanoparticle suspension was limited by its stability and difficulty in scaleup.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) Consequently, amorphous solid dispersion has become an increasingly utilized approach for improving the bioavailability of poorly water-soluble compounds. [4][5][6][7] In many cases, a supersaturated drug solution generated by amorphous solid dispersion is thermodynamically unstable and energetically tends to return to equilibrium via precipitation. 8) To maintain supersaturation, precipitation must be inhibited, in many cases by a polymeric precipitation inhibitor.…”
mentioning
confidence: 99%
“…[10][11][12] Recently, it was reported that composite nanoparticles could be fabricated by using supercritical fluid technology. 13 Carbon dioxide has been widely used as a supercritical fluid because it is nontoxic, nonflammable, and it has relatively low critical parameters (P c [critical pressure] =7.38 MPa, T c [critical temperature] =31.1°C).…”
Section: Introductionmentioning
confidence: 99%